Euphorbia hirta: Its chemistry, traditional and medicinal uses, and pharmacological activities - Kumar, Sunil; Malhotra, Rashmi; Kumar, Dinesh (Pharmacognosy Reviews, 2010)
The oldest remedies known to mankind are herbal medicines. India is known worldwide for its Ayurvedic treatment. Euphorbia hirta is often used traditionally for female disorders, respiratory ailments (cough, coryza, bronchitis, and asthma), worm infestations in children, dysentery, jaundice, pimples, gonorrhea, digestive problems, and tumors. It is reported to contain alkanes, triterpenes, phytosterols, tannins, polyphenols, and flavanoids. This review describes the medicinal properties, chemical constituents, and other important aspects of Euphorbia hirta.
Keywords: Antioxidant; antimalarial; antibacterial; euphorbia hirta